Development and validation of a questionnaire for assessing patients´ perceptions of interprofessional integration in health care. - Parra-Vega, Iris; Marqués-Sánchez, Pilar; Pelayo-Terán, José M.; Corral Gudino, Luis (Journal of Interprofessional Care)
The integration of care between primary, secondary, tertiary health care and social care needs to be interprofessional and patient-centered. The aim of this study was to develop and validate a questionnaire for measuring patients' perception of integration across health care teams and social services. Data for psychometric assessment of our questionnaire were collected from patients who attended at eleven Primary Care Centers and one tertiary referral Hospital in Spain from March to October 2018. The questionnaire was tested in a pilot study with 40 patients before being administered in a sample of 279 patients. The questionnaires were distributed in urban Health Centers, peri-urban or rural Health Centers (67%) and a tertiary referral hospital (33%). The questionnaire included 9 items that measured patient perceived experiences about care coordination, data accessibility and delivery of clinical information. The model explained 51% of the variation in the data and Cronbach's alpha was 0.8. Two factors comprising perception of coordination and assessment of patient-centered care were identified. The overall perception for integration was low. The reliability and validation of our questionnaire showed its potential as a valuable instrument for assessing patients' perception of the integration of care and can be used within the quality metrics to assess the success of integrated health care management programs.